Advances in antimicrobial peptides-based biosensing methods for detection of foodborne pathogens: A review. (June 2020) - Qiao, Zhaohui; Fu, Yingchun; Lei, Chunyang; Li, Yanbin
Abstract: Foodborne diseases caused by pathogens are great threats to human health. Rapid detection of foodborne pathogens at an early stage is imperative for preventing the outbreak of diseases. The identification and detection of foodborne pathogens by biosensors have attracted great attention due to their high sensitivity, nearly real-time quantification without enrichment and the possibility of on-site detection with easy-to-use format. As a promising alternative recognition element of biosensors, antimicrobial peptides (AMPs) with high stability and low cost have been widely studied in the detection of bacteria. In this review, we retrospect the advances on AMPs-based detection methods for foodborne pathogens including electrochemical, optical and piezoelectric methods as well as their integrations with nanomaterials. Considering the important roles of AMPs affinity in detection, the factors influencing AMPs affinity are introduced before the review of various AMPs-based methods. In addition, as a new promising technology, the microfluidics has been integrated with AMPs-based methods to detect foodborne pathogens. Finally, future perspectives and challenges in developing reliable and sensitive AMPs-based platforms are discussed.